Friends. Season 5 [videorecording (DVD)] - Aniston, Jennifer; Cox, Courteney, 1964-; Kudrow, Lisa; LeBlanc, Matt; Perry, Matthew, 1969-; Schwimmer, David, 1966- (Warner Bros. Entertainment Inc., 2019)
"Starting in London, finishing in Las Vegas and bookending with weddings in both places, Season five is memorable for everyone! Ross's overseas nuptials are off to a rocky start, Phoebe gives birth in the show's 100th episode, and the gang heads west to Sin City, where Joey hopes to land his big showbiz break!"--Container